The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1093/infdis/132.6.623
|View full text |Cite
|
Sign up to set email alerts
|

Human Responses to Two Decavalent Rhinovims Vaccines

Abstract: Two formalin-inactivated, decavalent rhinovirus vaccines were tested in humans for acceptability and antigenicity. Infectivity titers of the vaccine antigens were low and ranged from 10(1.5) to 10(5.5) 50% tissue culture infective doses/ml. There were minimal or no side effects to either vaccine. The first inoculation of one vaccine produced antigenic responses to 30% of the administered antigens. Limited testing for heterologous antibody responses to nonvaccine antigens showed scattered responses. These findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…However, in those studies which have assessed a significant number of serotypes, crossreactivity was shown to be somewhat limited because for example only 13 of 37 tested antisera from whole virus immunised rabbits neutralised a single other virus serotype [26]. The cross-reactive virus binding and virus neutralising antibody responses in humans are also somewhat variable between individuals [12 , 27,28]. In terms of protection against virus infection, secondary infection with a heterologous virus serotype could reduce the frequency and severity of symptoms similarly to a homologous virus reinfection in one study [29], but intramuscular inactivated vaccine provided no protection against cold symptoms or virus shedding following heterologous virus challenge in another [15].…”
Section: Antibody Cross-reactivity Amongst Hrvsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in those studies which have assessed a significant number of serotypes, crossreactivity was shown to be somewhat limited because for example only 13 of 37 tested antisera from whole virus immunised rabbits neutralised a single other virus serotype [26]. The cross-reactive virus binding and virus neutralising antibody responses in humans are also somewhat variable between individuals [12 , 27,28]. In terms of protection against virus infection, secondary infection with a heterologous virus serotype could reduce the frequency and severity of symptoms similarly to a homologous virus reinfection in one study [29], but intramuscular inactivated vaccine provided no protection against cold symptoms or virus shedding following heterologous virus challenge in another [15].…”
Section: Antibody Cross-reactivity Amongst Hrvsmentioning
confidence: 99%
“…A previous attempt at this strategy with formalin inactivated decavalent whole virus preparations however demonstrated rises in neutralising antibody titres to 40% of serotypes at best [27]. A huge number of virus types would also likely need to be contained in such a vaccine because, as noted above, it has been found that large numbers of strains circulate simultaneously, with for example over 100 genetically distinct strains having been found in a small paediatric cohort in just a 2 year period [22].…”
Section: Antibody Cross-reactivity Amongst Hrvsmentioning
confidence: 99%
“…By the late 1960s, over 50 HRV serotypes had been defined, and vaccination of volunteers did not result in heterologous neutralizing Abs. By the mid-1970s, the outlook for a HRV vaccine was dour, due the large number of serotypes, technical challenges associated with producing high valency vaccines, and poor performance of a decavalent, formalin-inactivated HRV vaccine, although the vaccine study was limited by low input titers of several HRV strains [51,52]. There is some cross-reactivity between HRV serotypes, and experimental infection of volunteers can result in protective immunity lasting at least one year [53,54].…”
Section: Hrv Species and Typesmentioning
confidence: 99%
“…In 1975, it was reported that two different 10-valent inactivated HRV preparations induced nAb titers to only 30-40% of the input virus types in recipient subjects 33 . However, the input titers of viruses prior to inactivation ranged from 10 1.5 to 10 5.5 TCID 50 per ml, and these were then diluted 10-fold to generate 10-valent 1.0 ml doses given i.m.…”
Section: Resultsmentioning
confidence: 99%
“…However, the input titers of viruses prior to inactivation ranged from 10 1.5 to 10 5.5 TCID 50 per ml, and these were then diluted 10-fold to generate 10-valent 1.0 ml doses given i.m. as prime and boost with no adjuvant 33 . We hypothesized that low input antigen doses are responsible for poor nAb responses to 10-valent inactivated HRV.…”
Section: Resultsmentioning
confidence: 99%